HADITH MEMORY LEARNING USING THE MOVEMENT METHOD FOR EARLY CHILDREN - Rizka Harfiani; Hasrian Rudi Setiawan (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of preparing this proceeding article is to provide information on learning to memorize hadiths that are easy for young children by using the movement method. This method can be practiced by teachers in early childhood education institutions. This research was conducted at RA. Ar-Rasyid, Sunggal District, Deli Serdang Regency. This study used a qualitative approach with a descriptive type. Data collection techniques were carried out by observation, interviews, and documentation. The analysis technique used is descriptive analysis. The research results obtained are that children can easily memorize hadiths using the movement method. The conclusion that can be drawn from this study is that the movement method is a suitable method and can be applied in learning to memorize hadiths for early childhood.